2017
DOI: 10.1039/c7mt00254h
|View full text |Cite
|
Sign up to set email alerts
|

Duodenal cytochrome b (Cybrd1) ferric reductase functional studies in cells

Abstract: Dietary non-heme ferric iron is reduced by the ferric reductase enzyme, duodenal cytochrome b (Dcytb), before absorption by the divalent metal transporter 1 (DMT1). A single nucleotide polymorphism (SNP rs10455 mutant) that is located in the last exon of the Dcytb gene was reported in C282Y haemochromatosis HFE subjects. The present work therefore investigated the phenotype of this mutant Dcytb in Chinese hamster ovary (CHO) cells. These cultured cells were transfected with either wild type (WT) or the SNP vec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…CYBRD1 is a ferrous ion-regulated reductase that activates multiple intracellular signaling pathways involved in transmembrane ferric ion transport [ 12 ]. CYBRD1 comprises 286 amino acid residues and six membrane-spanning domains [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CYBRD1 is a ferrous ion-regulated reductase that activates multiple intracellular signaling pathways involved in transmembrane ferric ion transport [ 12 ]. CYBRD1 comprises 286 amino acid residues and six membrane-spanning domains [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…CYBRD1 is a ferrous ion-regulated reductase that activates multiple intracellular signaling pathways involved in transmembrane ferric ion transport [ 12 ]. CYBRD1 comprises 286 amino acid residues and six membrane-spanning domains [ 12 ]. The amino acid sequence of CYBRD1 is 45%–50% similar to that of cytochrome b561, which facilitates electron transport across the membrane [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…as a member of the cytochrome family, cYBrd1 encodes an iron-regulated protein and exhibits ferric reductase activity (40). Furthermore, cYBrd1 has been demonstrated to serve a key role in dietary iron absorption (41). it has been shown that nec may affect the expression of cYBrd1 in the duodenal brush border membrane and contributes to the severe anemia associated with nec (42).…”
Section: Discussionmentioning
confidence: 99%
“…However, heme is rapidly catabolized by HO-1 to release the iron (Daher et al, 2017). Fe 3+ can be reduced into the Fe 2+ form by DCYTB, and Fe 2+ is imported by the apical DMT1 (Schlottmann et al, 2017). In the basolateral membrane of intestinal epithelial cells, ferritin (FPN) is the main iron exporter, transporting Fe 2+ .…”
Section: Iron Metabolism and Ferroptosismentioning
confidence: 99%